Autonomous conveyer gel driven by frontal polymerization. Issue 10 (26th November 2015) - Wang, Xiao‐Qiao; Liu, Nian; Wang, Cai‐Feng; Chen, Su
ABSTRACT: Autonomous mechanical mass transportation for cargos on the microscale with no need of continuous external powering is of great scientific and technological interest due to their extensive applications. However, it is still challenging to create a self‐driven system applicable to diverse micromaterial transportation demands. In this work, we developed a novel autonomous conveyer gel driven by frontal polymerization (FP). The chemical wave produced in FP was stable, and self‐propagating with a constant velocity, which can be easily monitored by thermal imaging or fluorescence labeling. We investigated the influence of the initiation temperature, swelling ratio of the gel substrate, and the size of the cargos on the motion of driven behavior. Results showed that the driving velocity can be well controlled by altering the initiation temperatures of FP. The swelling ratio and the size of the cargos had a key impact on the feasibility of self‐driven behavior. In addition, powerful driven capability by FP was demonstrated by successfully transporting cargos in series, and further applied for targeted synthesis of CdS nanocrystals. The methodology developed here provides an effective way to convert chemical energy to mechanical work, and may be useful in energy conversion and utilization, mass transportation and other applications. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 1323‐1331 Abstract : A series of autonomous conveyer gels were fabricated by frontal polymerization (FP), and exhibited a powerful capability for transporting gel microballoons. The transportation speed can be efficiently controlled by adjusting initiation temperature of the FP reaction. The autonomous transportation was further applied for the targeted synthesis of CdS nanocrystals.